Endocrine Function and Antiepileptic Drugs - J Gordon Millichap (Pediatric Neurology Briefs)
The effects of valproate (VPA) in 40, carbamazepine (CBZ) in 19, and oxcarbazepine (OXC) in 18 girls with epilepsy on growth and maturation were compared to 49 healthy untreated controls examined at 8 to 18 years of age at the Departments of Neurology, Pediatrics, and Radiology, University of Oulu, Finland.